Handbook of personality - "Pervin, Lawrence A.(ed.)" (New York, 2006)
Introduction - History of Modern Personality Theory and Research, Winter and Barenbaum Theoretical Perspectives - Human Nature and Individual Differences: The Evolution of Human Personality, Psychoanalytic Approaches to Personality, The Big Five Trait Taxonomy: History, Measurement, and Theoretical Perspectives, A Five-Factor Theory of Personality, Social Cognitive Theory of Personality, Integrating Dispositions and Processing Dynamics within a Unified Theory of Personality: The Cognitive Affective Personality System, Holistic Interactionism: A Perspective for Research on Personality Development.Interface with Other Fields - Behavioral Genetics and Personality, The Neuroscience of Personality, Personality Continuity and Change across the Life Course, On the Development of Personality, Personality and Psychopathology, On the Interface between Personality and Social Psychology, The Cultural Constitution of Personality. Content Areas - Temperament: A New Paradigm for Trait Psychology, The Psychological Unconscious, Naturalizing the Self, Personal Narratives and the Life Story, Personality and Motivation: Personal Action and the Conative Evolution, Emotion and Emotion Regulation, Stress, Coping, and Self-Regulatory Processes, Personality and Health: Dispositions and Processes in Disease Susceptibility and Adaptation to Illness, Attribution in Personality Psychology, Creativity and Genius, The Fields of Interpersonal Behavior. Featuring contributions from foremost authorities, this volume provides a complete survey of modern personality theory, brings major theoretical perspectives into focus, and analyzes the current state of the science. Particular emphasis is given to the dynamic interface between personality psychology and other disciplines, with the recent explosion of knowledge about biological aspects of personality reflected in chapters on evolutionary psychology, behavioral genetics, neuroscience, and temperament. Major research is also presented on such defini
Keywords: Personality-Handbook